Praktek Monopoli dan Persaingan Usaha pada Kasus Kenaikan Harga Produk pada Masa Covid 19 Berdasarkan Undang-Undang Nomor 5 Tahun 1999 - Isabel Sihombing, Felicia; Saputra Simbolon, Michael; Ramadhani Siregar, Naurah; Alawiyah Matondang, Khairani (PENG: Jurnal Ekonomi dan Manajemen, 2025)
The COVID-19 pandemic had a significant impact, especially in the economic sector, leading to price increases in health products such as masks, hand sanitizers, and personal protective equipment (PPE). This study aims to understand the practices of monopoly and unfair business competition during the pandemic, particularly related to the price increases of health products. The research uses a legal approach to examine the existing regulations and how these rules are implemented in practice. The results show that some business actors raised prices unreasonably by setting high prices together with their competitors (price fixing) and abusing their position to dominate the market, which violates Law No. 5 of 1999. The study also highlights the role of the Business Competition Supervisory Commission (KPPU) in monitoring and taking action against violations. However, the effectiveness of law enforcement is still weak due to the limited authority of the KPPU. This study recommends granting the KPPU greater authority, strengthening supervision, and implementing stricter sanctions to ensure healthy business competition and protect consumers.